A clinico-demographic profile of 110 male patients with genital ulcer(s) - Kumar, Piyush; Mondal, Avijit; Chowdhury, Satyendra Nath; Das, Nilay Kanti; Datta, Pijush Kanti; Gharami, Ramesh Chandra (Journal of Pakistan Association of Dermatologists, 2018)
Objective To assess the magnitude of male genital ulcer (MGU) and its clinico-demographic profile in patients attending dermatology OPD and STI clinic of a tertiary care hospital in the eastern part of India. Methods The study was institution-based cross-sectional descriptive study conducted over a period of one year. All the male patients presenting to Dermatology OPD and STI clinic with complaints of genital lesions were screened for genital ulcer/s. Those having genital ulcer and giving consent for participating in the study were included in the study. At the end of study period, data were analyzed. Results 110 patients with MGU among 22,528 male patients attending Dermatology OPD and STI clinic were included in study and relative prevalence rate was calculated as 4.88 per 1000. Non-sexually transmitted ulcers (non-STU) [65.5%] were leading cause of MGU. Among sexually transmitted ulcers (STU), genital herpes was the most common disease. Dermatitis-related ulcer, scabies related ulcer, and Zoon’s balanitis (plasma cell balanitis) were most common non-STU. Positive history of sexual exposure was found in around 53.2%, 97.4% and 22.2% of MGU, STU and non-STU, respectively. Commercial sex workers were the major sex partner in both STU and non-STU groups. Conclusion Non-sexually transmitted ulcers were more common than sexually transmitted ulcers. History of sexual exposure was seen in both STU, and non-STU. Hence, history of sexual exposure should not bias clinician towards making a diagnosis of STU.